Profiling of biological and environmental risk factors in immunogenetic subgroups of chronic lymphocytic leukemia - Czech national study - Stranska, Kamila; Plevova, Karla; Skuhrova Francova, Hana; Skabrahova, Hana; von Jagwitz-Biegnitz, Magdalena; Radova, Lenka; Panovska, Anna; Hrobkova, Stanislava; Brychtova, Yvona; Urbanova, Renata; Smolej, Lukas; Simkovic, Martin; et al. (Biomedical papers, 2020)
Aims: This is a nation-wide survey of chronic lymphocytic leukemia (CLL) patients at six large hematology centers in the Czech Republic. The aim was to identify specific populations, social, and health characteristics of CLL subgroups divided according to the immunogenetic features of their B cell receptors (BCRs) and clonality. Patients and Methods: Questionnaires directed to specific health, social, and environmental conditions were collected in a cohort of 573 CLL patients. For these patients, immunoglobulin heavy chain gene rearrangements were also analyzed in order to gain information about their clonality, IGHV mutational status, and the presence of stereotyped BCRs. Data extracted from the questionnaires were analyzed statistically in the context of immunogenetic features of the cohort. Results: There were no statistically significant differences in the data collected in the survey between patients with mutated and patients with unmutated IGHV. However, patients with oligoclonal CLL reported health conditions such as hypercholesterolemia, hypertension, herpes simplex, tumors, and also, separately, CLL in 1st degree relatives, more often than their monoclonal counterparts. In patients with stereotyped BCRs, we found more frequent alcohol consumption and gastric infections in subset #1 cases and frequent cholecystectomies and familial CLL in subset #2 cases. Conclusion: To the best of our knowledge, this study is the first to investigate CLL immunogenetic features and clonality in the context of epidemiological data. We reported statistically significant associations suggesting the influence of certain health and social conditions on a number of clonal populations expanding in CLL and also on characteristic BCR features, especially stereotypy.
Keywords: chronic lymphocytic leukemia; B-cell receptor; clonality; questionnaire; patient history; biological risk factor